Combinatorial Optimization and Applications 10th International Conference, COCOA 2016, Hong Kong, China, December 16-18, 2016, Proceedings - Chan, T-H. Hubert; Li, Minming; Wang, Lusheng (Theoretical Computer Science and General Issues, 2016)
This book constitutes the refereed proceedings of the 10th International Conference on Combinatorial Optimization and Applications, COCOA 2016, held in Hong Kong, China, in December 2016. The 60 full papers included in the book were carefully reviewed and selected from 122 submissions. The papers are organized in topical sections such as graph theory, geometric optimization, complexity and data structure, combinatorial optimization, and miscellaneous.